REALISING 21ST CENTURY EDUCATION THROUGH TECHNOLOGY AND INNOVATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 14 November 2016 – At present, education for students should be about 'Rethinking Teaching, Redesign Learning' in order to move forward into future endeavours and also to motivate and inspire students to ensure their success in life.